Is an infectious trigger always required for primary hemophagocytic lymphohistiocytosis? Lessons from in utero and neonatal disease. Issue 11 (1st August 2018) - Heeg, Maximilian; Ammann, Sandra; Klemann, Christian; Panning, Marcus; Falcone, Valeria; Hengel, Harmut; Lehmberg, Kai; zur Stadt, Udo; Wustrau, Katharina; Janka, Gritta; Ehl, Stephan
Abstract: In this report, we evaluate the hypothesis that hemophagocytic lymphohistiocytosis in patients with defects of lymphocyte cytotoxicity is usually triggered by infections. We show that in the majority of patients, extensive virus PCR panels performed in addition to routine microbiological investigations remain negative and summarize 25 patients with onset of hemophagocytic lymphohistiocytosis in utero or within the first 10 days of life, in none of which an associated bacterial or viral infection was reported. These observations, even though preliminary, invite to consider a key role of lymphocyte cytotoxicity in controlling T‐cell homeostasis also in the absence of apparent infectious stimuli.